Decision making in child protection: An international comparative study on maltreatment substantiation, risk assessment and interventions recommendations, and the role of professionals' child welfare attitudes. (November 2015) - Benbenishty, Rami; Davidson-Arad, Bilha; López, Mónica; Devaney, John; Spratt, Trevor; Koopmans, Carien; Knorth, Erik J.; Witteman, Cilia L.M.; Del Valle, Jorge F.; Hayes, David
Abstract: Child welfare professionals regularly make crucial decisions that have a significant impact on children and their families. The present study presents the Judgments and Decision Processes in Context model (JUDPIC) and uses it to examine the relationships between three independent domains: case characteristic (mother's wish with regard to removal), practitioner characteristic (child welfare attitudes), and protective system context (four countries: Israel, the Netherlands, Northern Ireland and Spain); and three dependent factors: substantiation of maltreatment, risk assessment, and intervention recommendation. The sample consisted of 828 practitioners from four countries. Participants were presented with a vignette of a case of alleged child maltreatment and were asked to determine whether maltreatment was substantiated, assess risk and recommend an intervention using structured instruments. Participants' child welfare attitudes were assessed. The case characteristic of mother's wish with regard to removal had no impact on judgments and decisions. In contrast, practitioners' child welfare attitudes were associated with substantiation, risk assessments and recommendations. There were significant country differences on most measures. The findings support most of the predictions derived from the JUDPIC model. The significant differences between practitioners from different countries underscore the importance of context in child protection decision making. Training should enhance practitioners' awareness of the impact that their attitudes and the context in which they are embedded have on their judgments and decisions.